Immunometabolic biomarkers of inflammation in Behçet's disease: relationship with epidemiological profile, disease activity and therapeutic regimens. (24th February 2016) - Cantarini, L.; Pucino, V.; Vitale, A.; Talarico, R.; M. Lucherini, O.; Magnotti, F.; De Rosa, V.; Galgani, M.; Alviggi, C.; Marone, G.; Galeazzi, M.; Matarese, G.
Summary: Behcet's disease (BD) is a systemic inflammatory disease with a still unclear pathogenesis. Although several inflammatory molecules have been studied, current biomarkers are largely insensitive in BD and unable to predict disease progression and response to treatment. Our primary aim was to explore serum levels of soluble CD40 L (sCD40L), soluble intracellular adhesion molecule (sICAM‐1), monocyte chemoattractant protein‐1 (MCP‐1), myeloperoxidase (MPO), leptin, resistin, osteoprotegerin (OPG), soluble type 1 tumour necrosis factor receptor (sTNFR), interleukin (IL)−6 and serum amyloid A (SAA) serum concentration in a cohort of 27 BD patients. The secondary aim was to evaluate potential correlations between the putative circulating biomarkers, demographic profile of patients, the status of disease activity, the specific organ involvement at the time of sample collection and different therapeutic regimens. Serum concentrations of sTNFR ( P = 0·008), leptin ( P = 0·0011), sCD40L ( P < 0·0001) and IL‐6 ( P = 0·0154) were significantly higher in BD patients than in HC, while no difference was found in MCP‐1, MPO and resistin serum levels. Moreover, we observed significantly higher sTNFR serum concentrations in BD patients presenting inactive disease than HC ( P = 0·0108). A correlation between sTNFR and age was also found, with higher levels in patients over 40 years than HC ( P = 0·0329). Although further research is warranted to elucidate the role of circulating biomarkers, some of that may contribute to the understanding of the physiopathology processes underlying BD activity and damage as well as to provide useful tools for prognostic purposes and a personalized treatment approach.